2015
DOI: 10.1074/jbc.m115.662916
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomic Profiling Reveals That Dysregulated Glycolysis Stemming from Lack of Salvage NAD+ Biosynthesis Impairs Reproductive Development in Caenorhabditis elegans

Abstract: Background: Loss of NADϩ salvage biosynthesis causes a reproductive delay in C. elegans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
(70 reference statements)
1
25
2
Order By: Relevance
“…A, supplementation of QA to pnc-1(pk9605) mutants restores the gonad developmental delay but has no effect on umps-1(ok2703);pnc-1(pk9605) animals, whereas supplementation of NA restores gonad development in both genetic backgrounds. Note that the penetrance of the gonad development phenotype is influenced by food type (15,18). The penetrance is lower (more normal animals) in this experiment than that reported in Fig.…”
Section: Umps-1 Contributes To Nad ؉ Biosynthesiscontrasting
confidence: 58%
See 2 more Smart Citations
“…A, supplementation of QA to pnc-1(pk9605) mutants restores the gonad developmental delay but has no effect on umps-1(ok2703);pnc-1(pk9605) animals, whereas supplementation of NA restores gonad development in both genetic backgrounds. Note that the penetrance of the gonad development phenotype is influenced by food type (15,18). The penetrance is lower (more normal animals) in this experiment than that reported in Fig.…”
Section: Umps-1 Contributes To Nad ؉ Biosynthesiscontrasting
confidence: 58%
“…We previously reported that salvage NAD ϩ synthesis is critical for the normal progression of gonad development, for full fecundity, and for efficient glucose metabolism in the cytosol (12,15,17,18). Interestingly, loss of NAD ϩ de novo synthesis also resulted in decreased progeny production compared with wild type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given conservation of NAM-receptor interactions across these phyla, we expect Brugia OSM-9 orthologs to also respond to NAM. However, the pharmacology and subunit interactions of Brugia OSM-9 may differ (e.g., filarial parasites do not have a homolog of ocr-4 ( Figure 3A)), and NAM is an endogenous metabolite in C. elegans that has pleiotropic effects (54,(56)(57)(58)(59)(60) . This compelled us to use a genetic approach to more directly test whether Brugia OSM-9 and TAX-4 are involved in parasite chemotaxis behavior.…”
Section: Bp-osm-9 and Bp-tax-4 Rnai Inhibits Chemoattraction Of Infecmentioning
confidence: 99%
“…In human cancer cells and C. elegans the depletion of NAD levels during NAMPT inhibition is associated with decreased glycolytic flux through attenuation of GAPDH activity . This effect impairs both the generation of ATP and cycling of NAD(H).…”
Section: Resultsmentioning
confidence: 99%